University Mission Statements and Sustainability Performance. (26th July 2018) - Lopez, Yvette P.; Martin, William F.
ABSTRACT: This paper examines the relationship between university mission statements and sustainability practices by institutions of higher education. We examine mission statement constructs and the degree to which higher educational institutions meet specific sustainability criteria in line with the College Sustainability Report Card. Our sample consists of 347 universities from the Sustainable Endowment Institute's (2011) Green Report Card. Previous research suggests that mission statements are essential for superior organizational performance outcomes. We examine the relationship between university mission statement content and sustainability practices. Findings indicate that the greater the number of specific terms used in the university mission statements, the higher the statistical likelihood that those universities had higher sustainability ratings. Findings also indicate that private institutions and nonreligious‐affiliated institutions are more likely to include sustainability constructs in their mission statements than colleges and universities with religious affiliation and public institutions. Several propositions to guide future research are discussed.